Optimization of a downdraft furnace for rice straw-based heat generation - Migo-Sumagang, Maria Victoria P.; Van Hung, Nguyen; Detras, Monet Concepcion M.; Alfafara, Catalino G.; Borines, Myra G.; Capunitan, Jewel A.; Gummert, Martin (Elsevier, 2020)
Open-field burning, a widely used treatment and disposal method for rice straw, poses severe health and environmental problems due to the release of toxic gases and loss of significant soil nutrients. Hence, alternative techniques must be explored. In this study, the use of rice straw as feedstock for a downdraft small-scale furnace to produce heated air for paddy drying was investigated. A two-level factorial experiment was initially implemented using differently conditioned rice straw types, rice straw feed rates, and drying airflow rates. Optimization results using Response Surface Methodology (RSM) showed there is no significant difference in the drying air efficiency using either loose or baled straw. The optimum conditions found were at a rice straw feed rate of 20.67 kg hr-1 and drying airflow rate of 3.03 m3 s-1, resulting in a drying air efficiency of 86.1%, and an increase in drying air temperature of 18.41 oC which was sufficient for paddy drying applications. At the optimum conditions, the average CO and NOx concentrations measured inside the dryer simulator were 76.57 and 2.93 ppm, respectively. The results of this research can be used for pilot studies in actual agricultural cooperatives, as well as provide inputs to life cycle analysis